Dopamine vs noradrenaline: inverted-U effects and ADHD theories. - Levy F (Australian & New Zealand Journal of Psychiatry, 2009)
The aim of the present study was to review the dopamine theory of attention-deficit-hyperactivity disorder (ADHD), in light of recent use of noradrenergic therapies. A historical review of pharmacological theories of ADHD was conducted, including inverted-U, spatial working memory and neural circuit aspects. Pharmacological advances, including animal and human studies of dopaminergic and noradrenergic mechanisms at the prefrontal cortex (PFC), indicate that alpha-2A adrenoreceptor stimulation results in increased dendritic firing during delay periods for preferred directions, while moderate levels of D1 receptor stimulation result in reduction of delay-related firing to non-preferred directions, allowing representational control in the PFC. Recent studies of the COMT val/met gene and stimulant medication response may help explain variation in inverted-U responses in individuals. Further studies utilizing delay-related firing paradigms should be useful in the investigation of attentional syndromes, and responses to newer pharmacological treatments.